(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article will consider the economic nature of liquidation operations in the activities of commercial banks and the basis for its application in banking activities, as well as the comparison of liquidity with classical banking operations and the determination of the next perspectives of liquidation operations.